A downhole CO2 sensor to monitor CO2 movement in situ for geologic carbon storage. (December 2016) - Wang, Sai; San, Jingshan; Yu, Jianjia; Lee, Robert; Liu, Ning
Highlights: A downhole CO2 sensor was developed and prepared. The CO2 sensor could measure dissolved CO2 concentration under high pressure. The sensor could detect CO2 movement in CO2 /brine core flooding tests. The sensor could be reused by brine flooding after CO2 /brine flushed the core. Abstract: This paper describes how a downhole CO2 chemical sensor was prepared for use in determining the concentration of CO2 in water, particularly in harsh, high-pressure environments such as those found in geological formations considered for the geologic storage of CO2 . The sensor consisted of a pair of Ir/IrOx and Ag/AgCl electrodes, a gas-permeable membrane, a bicarbonate-based internal electrolyte solution, and porous stainless steel as supporting material. The sensor was tested in the solution with different concentrations of CO2 and displayed very good CO2 sensing performance under pressures of 1000, 2000, and 3000 psi. A linear relationship between the sensor response potential and the logarithm of the CO2 concentration was obtained for the sensor under different pressures. Reproducibility of the sensor was examined and the results indicated that the sensor displayed excellent reproducibility. CO2 /brine core flooding tests were carried out to evaluate the performance of the CO2 sensor in simulate CO2 storage process. The results indicated that the sensor could detect CO2 movement in the tests. Further studies showed that the sensor could be reused by brine flooding after CO2 /brine flushed the core. The results of the core flooding tests demonstrated that the sensor had potential application for CO2 monitoring in carbon storage.